'The vandals at home': Antonio Cederna's denunciation of the devastation of Italian cities in the postwar period. Issue 5 (19th October 2016) - Bonomo, Bruno
Abstract: Writing for the influential magazine Il Mondo, Antonio Cederna relentlessly denounced the projects and works that endangered Italy's historical and landscape heritage in a period – the 1950s and 1960s – characterized by processes of change that were as intense as they were disordered and contradictory. The battles he waged against the danger of Italian cities being tampered with by those whom he called 'the vandals at home' had a significant impact on urban development. In addition, his discourse left a deep and enduring trace in Italian journalism, urban planning and historiography. This article focuses on the early period of Cederna's journalistic activity: it delineates the core features of his denunciation, paying as much attention to its contents as to the form and manner in which it was expressed, and it assesses the outcome and legacy of his press campaigns both on a material and a political-cultural level.